2020
DOI: 10.1037/xge0000698
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive control across adolescence: Dynamic adjustments and mind-wandering.

Abstract: Models of cognitive development suggest that cognitive control, a complex construct that ensures goal-directedness even in the face of distractions, is still maturing across adolescence. In the present study, we investigated how the ability to dynamically adjust cognitive control develops in this period of life, as indexed by the magnitude of the congruency sequence effect (CSE) in conflict tasks, and how this ability might relate to lapses of attention (mindwandering, MW). To these ends, participants from fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 109 publications
(179 reference statements)
6
19
1
Order By: Relevance
“…Note: ✓ = support for the presence of the congruency sequence effect (CSE); × = support against the presence of the CSE; -= inconclusive findings. (Aschenbrenner & Balota, 2017), or the correlation between the size of the effect in different tasks across subjects (Gyurkovics et al, 2020;Whitehead, Brewer, & Blais, 2019). Our results neither support, nor contradict these findings.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Note: ✓ = support for the presence of the congruency sequence effect (CSE); × = support against the presence of the CSE; -= inconclusive findings. (Aschenbrenner & Balota, 2017), or the correlation between the size of the effect in different tasks across subjects (Gyurkovics et al, 2020;Whitehead, Brewer, & Blais, 2019). Our results neither support, nor contradict these findings.…”
Section: Discussioncontrasting
confidence: 99%
“…This is because even when considered only numerically, the Simon and the prime-probe tasks do not show larger effects than the Stroop and the flanker tasks. It is, however, worth noting that Gyurkovics, Stafford, & Levita (2020) found the CSE to be smaller in a confoundminimized flanker task compared to a confound-minimized Simon task in a sample of adolescents and young adults. This is in line with the findings of the original Weissman et al study and the non-significant pattern observed in the present study.…”
Section: Discussionmentioning
confidence: 85%
“…Group-level target sample sizes were set to match those in Gyurkovics et al (2019), i.e., approximately 30. This still reflects an increase in statistical power for the conflict task analyses compared to that study, as the number of observations in the task was more than doubled (160 vs. 72 trials by condition).…”
Section: Participantsmentioning
confidence: 99%
“…Yet developmental studies of the CSE are scarce, and thus far they have typically found no significant differences in the magnitude of the effect between adolescents and adults (Waxer and Morton 2011;Larson, Clawson, et al 2012;Cragg 2016;Smulders et al 2018;Gyurkovics et al 2019). These studies mostly focused on overt behaviour, and, with the exception of Cragg (2016) and Gyurkovics et al (2019), used tasks that contained feature repetitions and stimulusresponse contingencies limiting the scope of conclusions regarding top-down control that can be drawn from these findings (for a discussion of the effect of these confounds on the CSE, see e.g., (Duthoo et al 2014)).…”
mentioning
confidence: 99%
See 1 more Smart Citation